PERBEDAAN PENGARUH LATIHAN IMAGERY DAN TANPA LATIHAN IMAGERY TERHADAP PENINGKATAN KEMAMPUAN SHOOTING GAME ATLET PETANQUE UNDIKMA - Muhammad Ridwan Lubis; Andi Gilang Permadi (Lembaga Penelitian dan Pendidikan Mandala, 2020)
This research is motivated by the inconsistency in the shooting ability of athletes in shooting game matches in the game of petanque sports both at the regional and national levels. This study aims to determine the effect of imagery training and concentration on improving the shooting abilities of Undikma petanque athletes. This study uses an experimental method with the